Toxicidade aguda e respostas metabólicas e hematológicas do pacu (Piaractus mesopotamicus, Holmberg, 1887) exposto a concentração sub-letal de triclorfon e recuperação - Venturini, Francine Perri (2010)
Parasitosis in fishes is a relevant problem in aquaculture. Besides, the organophosphate trichlorfon (2,2,2-trichloro-1-hydroxyethyl phosphonate) is amongst the most used medicine in farming of fishes. Due to trichlorfon use in fish parasitosis control, including pacu (Piaractus mesopotamicus), in brazilian and worldwide aquaculture, it is necessary to study the effects of this organophosphorus compound related to toxicity and metabolic biochemical parameters. The aim of this work was to evaluate trichlorfon acute toxicity (LC(I)50;96h) to P. mesopotamicus and histopathological effects of this exposition; detect metabolic changes in juvenile pacu (P. mesopotamicus) exposed to trichlorfon sub-lethal concentration (10% LC (I) 50;96h); and evaluate metabolic changes after seven and 14 days of recovery. Estimated (LC (I)50;96h) of trichlorfon to alevin was 0.04mg/L; to juvenile fish was 0.07 mgL-1. Histological evaluation showed adaptive alterations, aiming to limit xenobiotic entrance; liver alterations aimed an increase in blood influx, consequently increasing detoxication; kidney alterations indicate excretion increase and skin presented cromatophore migration to superficial folds. After sub-lethal exposure, pacu presented a decrease in hemoglobin, after seven days recovery it was recorded a decrease in MCH and after 14 days recovery analysis showed a decrease in hematocrit. Metabolic alterations observed after sub-lethal expositions and recovery indicated efforts aiming to homeostatic maintenance trough energy production. Brain and muscle AChE activity decreased, regaining the control values after 14 day of recovery in xenobiotic free water.